Legal Construction of Nursing Accountability in Circumcision Practice - Panggih Sediyo; Isharyanto Isharyanto; Arief Suryono (Journal of Health Policy and Management, 2018)
Background: Circumcision is one of the surgical practices often performed by nurses in rural and urban areas. Minister of Health Decree No. 1239 of 2001 on the registration and practice of nurses has not provided clarity on the limits of authority and legal protection for certain nurses. Many nurses provide services in the community that are not in accordance with the rules and authority.Subjects and Method: This was a normative study with statute, case study, and conceptual approach. Legal materials were collected using document review. Legal materials were analyzed by describing the problem under study.Results: Article 65 of Law Number 36 the Year 2014 on Health Personnel provides delegation of authority from the doctor to the nurse if the doctor cannot perform a medical service, provided that the physician is obliged to provide clear written authority delegation to perform the medical service. Regulation of the Minister of Health of the Republic of Indonesia No. 17 of 2013 on Amendment to Regulation of the Minister of Health No. Hk.02.02/Menkes/148/I/2010 Concer